2007
DOI: 10.1007/s00396-007-1733-6
|View full text |Cite
|
Sign up to set email alerts
|

Solvent retention in thin polymer films studied by gas chromatography

Abstract: Thin polystyrene films were produced by spin coating from solutions in toluene. The amount of solvent retained in the films after drying for different times was measured using gas chromatography. Whereas for thicker films (thickness > 200 nm), the relative amount of solvent in the films is less than a few percent, the proportion of toluene increases significantly in thinner films. The thickness dependence of the mass of retained solvent shows that the solvent is mainly retained at the polymer-substrate interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 65 publications
(89 reference statements)
7
60
0
Order By: Relevance
“…This is corroborated by research that showed that solvent removal from polymeric thin films is not trivial [37,38]. This article explores how the initial morphology of the P3HT:PCBM BHJ layer can be controlled through the use of solvent additives, how these impurities affect the thermal stability of the BHJ morphology, and device performance over time.…”
Section: Introductionmentioning
confidence: 49%
“…This is corroborated by research that showed that solvent removal from polymeric thin films is not trivial [37,38]. This article explores how the initial morphology of the P3HT:PCBM BHJ layer can be controlled through the use of solvent additives, how these impurities affect the thermal stability of the BHJ morphology, and device performance over time.…”
Section: Introductionmentioning
confidence: 49%
“…In particular, based on the comparison of the dPS-PMMA-OH and PMMA-PS-SH results, the presence of residual solvent in films post washing was hypothesized to have a significant effect. Reports in the literature have noted that both the content of solvent in very thin films is relatively high 29 and that the solvent can influence phase behavior. 30 To test this hypothesis, a single SCFT calculation was performed on a tethered diblock copolymer system (L/aN 1/2 = 0.45) in the presence of solvent.…”
Section: Resultsmentioning
confidence: 99%
“…35 However, it might not be a contradiction because García-Turiel and Jérome investigated annealed PS films, whereas our study focuses on untreated films probed directly after spin-coating.…”
Section: Influence Of Film Thicknessmentioning
confidence: 95%